A questão do saneamento no espaço rural: uma abordagem sócioambiental em três localidades rurais no município de Nova Palma, RS - (:unkn) unknown (Universidade Federal do Pampa, 2014)
The generation of waste can be considered an environmental issue, as it relates to public health, since it is part of sanitation along with the treatment of water and wastewater, has an impact on the preservation and / or conservation of natural resources, especially , in relation to water sources. The present study aims to conduct a survey on socioeconomic issues of families of three rural localities of the municipality of Palma Nova, RS (Bom Retiro, Linha Um and Rincão Santo Antônio) covering the use of pesticides and sanitation including pertinent questions about trash, water and sewer. For this, an exploratory and descriptive study was performed using a structured questionnaire completed by the head of the family and based on environmental conditions: the existence of collection and / or destination of household waste, the selective collection system, sewage disposal, source and treatment water consumption, use and destination of agrochemical containers on their properties from 65 families. After performing the study it was found that the majority of households in the three localities studied obtains water from springs on the farm itself, and in most cases without treatment, except for some households that reported the use of filtration and / or chlorination; the trash the three localities is not collected, being burned or buried in the vast majority practice seen by the respondents, a more acceptable technique when compared to eliminate the open. Additionally, there is a notorious awareness by owners of the three rural localities, on the fate of pesticide containers used in tobacco farming, being that they are returned by farmers to the tobacco and / or by local farmers cooperative companies. With this, one realizes that an awareness to residents of three rural localities emphasizing how to properly manage waste from their homes is necessary, besides seeking alternatives to reuse solid waste in order to reduce the volume of waste and prevent or decrease the contamination, including the proper handling and disposal of pesticide containers, for example, and environmental degradation, taking guidance on the correct recycling of organic waste, and all water care (origin, processing and utilization).
Keywords: Gestão de resíduos; Saneamento básico; Propriedades rurais; Waste Management; Basic sanitation; Rural Properties; CNPQ::CIENCIAS SOCIAIS APLICADAS